2010
DOI: 10.1007/s10514-010-9210-3
|View full text |Cite
|
Sign up to set email alerts
|

A Midsummer Night’s Dream (with flying robots)

Abstract: Seven flying robot "fairies" joined human actors in the Texas A&M production of William Shakespeare's A Midsummer Night's Dream. The production was a collaboration between the departments of Computer Science and Engineering, Electrical and Computer Engineering, and Theater Arts. The collaboration was motivated by two assertions. First, that the performing arts have principles for creating believable agents that will transfer to robots. Second, the theater is a natural testbed for evaluating the response of unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 20 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Movement has been considered in the context of robots and theater in a number of works and position papers (Hoffman, 2005;Hoffman, Kubat, & Breazeal, 2008;Knight, 2011;Murphy et al, 2010). In early robotic installation art, abstract motion has also been used for expressive effect and interactive communication with audiences (Inhatowicz, 1970).…”
Section: 21mentioning
confidence: 99%
“…Movement has been considered in the context of robots and theater in a number of works and position papers (Hoffman, 2005;Hoffman, Kubat, & Breazeal, 2008;Knight, 2011;Murphy et al, 2010). In early robotic installation art, abstract motion has also been used for expressive effect and interactive communication with audiences (Inhatowicz, 1970).…”
Section: 21mentioning
confidence: 99%
“…Previous HRI studies [14], [16] have used remote-controlled aerodynes, which offer impressive maneuverability and speed and can carry sizable payloads, but our eventual goal is to create an autonomous platform, which must be safe. A quadropter was tested, but seemed difficult to operate near a human.…”
Section: A Safetymentioning
confidence: 99%
“…As a result, in the above study, people reported being frightened of the robot used. Another study sought to provide communication capability in a theater play by pairing flying robots with human actors [14], but this approach may not be convenient for contexts in which a robot's autonomy is desired.…”
mentioning
confidence: 99%
“…Consequently, challenges in plays with robots that involve human actors are real-time responsiveness, human-robot coordination, and managing a shared common space and resources (Hoffman, 2011). Murphy et al (2011) present the play "A Midsummer Night's Dream" by William Shakespeare that involves seven flying robot and human actors on the same stage. Authors show that the audience learned how to interpret the robot behaviors based on the actors' reactions.…”
Section: Expression Of Emotions and Intentions In Nonanthropomorphic mentioning
confidence: 99%